Implementasi Promosi Kesehatan Untuk Mendorong Aktivitas Fisik Dan Kesegaran Jasmani Pada Remaja - Nurul Aisyiyah Puspitarini; Ronasari Mahaji Putri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Health promotion regarding the importance of physical activity for students' physical fitness at Universitas Tribhuwana Tunggadewi Malang plays a crucial role in fostering healthy lifestyle habits among students. Regular physical activity provides numerous benefits, including improving physical fitness, strengthening muscles and bones, and enhancing overall body endurance. In addition, exercise is also important for maintaining students’ mental health by helping to reduce stress, anxiety, and depression, which are commonly experienced during the academic period. Health promotion programs focused on physical activity can encourage students to develop sustainable healthy lifestyle habits. Through activities such as group exercise, fitness sessions, or campus-based sports classes, students are motivated to be more physically active. These activities not only improve physical fitness but also strengthen the sense of community among students. Support from the university enables active lifestyle habits to become an integral part of students’ daily lives, thereby contributing positively to both their physical and mental well-being. The results of this community service activity showed that all participating students attended the educational sessions from start to finish, demonstrating their enthusiasm and awareness of the importance of physical activity for maintaining health.